On the Causal Link between Financial Development and Economic Growth: Case of Jordan - AbuAl-Foul, Bassam (2016)
This paper empirically examines the causal relation between financial development and economic growth in the case of Jordan for the period 1965 to 2004. That is, the paper attempts to provide answers to the following questions: a) Does financial development promotes economic growth? Or b) Does economic growth promotes financial development? Using Toda and Yamamoto (1995) Granger-no-causality model, the results reveal that there is a uni-directional Granger causality from economic growth to financial development (as defined by log (DC/GDP)).